Influence of Annealing and Compaction on Enhancing the Temperature and Strain Sensitivities of Multi-Walled Carbon Nanotube (MWCNT) Films - Hassan, Rufaydah (AUC Knowledge Fountain, 2022)
Carbon nanotubes (CNTs) possess superior thermal, electrical, and mechanical properties. When CNTs undergo particular fabrication procedures, they transform from a nanoscale form into macroscopic thin sheets referred to as buckypapers (BPs). The main idea behind using BP is to facilitate the handling of CNTs without losing their exceptional properties. Additionally, BPs showed potential for being the used material in strain and temperature applications thanks to their thermal stability, flexibility, high sensitivity, and the ability to conform to any complex structure. In the current study, the multi-walled carbon nanotube (MWCNT) thin films were prepared using the vacuum filtration technique. Following the fabrication procedure, BPs were subjected to a combination of different treatments involving annealing, exposure to a boiling solvent, and compaction. A series of experimental tests, including loading/unloading, heating/cooling, and combining strain and temperature effects at the same time, were carried out to assess the piezoresistivity as well as the temperature sensitivity of the BP. The morphology of the BPs was examined using Scanning Electron Microscopy (SEM). Moreover, the fracture morphology of the BP was obtained by the tensile stage. The results indicate that BPs are highly sensitive to temperature and mechanical strain. Moreover, CNT thin films can exhibit a higher sensitivity when subjected to specific treatments, such as annealing and compaction. The improvement was confirmed by the obtained microstructure by SEM and quantified by the obtained empirical gauge factor (GF) values and the temperature coefficient of resistance (TCR) values.